Organic fertilizer improved the lead and cadmium metal tolerance of Eucalyptus camaldulensis by enhancing the uptake of potassium, phosphorus, and calcium - Ouyang, Linnan; Chen, Shaoxiong; Yang, Wentao; Zheng, Jiaqi; Ye, Lingshuai; Liu, Qiang; Yang, Jiaqi (Frontiers in Plant Science, 2024)
Phytoremediation is a strategy for the amelioration of soil heavy metal contamination that aligns with ecological sustainability principles. Among the spectrum of phytoremediation candidates, woody plants are considered particularly adept for their substantial biomass, profound root systems, and non-participation in the food chain. This study used Eucalyptus camaldulensis -a tree species characterized for its high biomass and rapid growth rate -to assess its growth and metal uptake in mining tailings. The results as follows: Exposure to heavy metals reduced the E. camaldulensis uptake of potassium (K), phosphorus (P), and calcium (Ca). Heavy metal stress negatively affecteds the biomass of E. camaldulensis. Lead (Pb) primarily accumulated in the roots, while cadmium (Cd) predominantly accumulated in the stems. The application of organic fertilizers bolstereds the stress tolerance of E. camaldulensis, mitigating the adverse impacts of heavy metal stress. A synergistic effect occurred when organic fertilizers were combined with bacterial fertilizers. The plant's enrichment capacity for Cd and its tolerance to Pb was augmented through the concurrent application of bacterial and organic fertilizers. Collectively, application of organic fertilizers improved heavy metal tolerance of E. camaldulensis by enhancing uptake of K, P, and Ca and elevating content of glutathione peroxidase (GPX) and gibberellin acid (GA) in roots. These findings provided nascent groundwork for breeding of E. camaldulensis with enhanced heavy metal tolerance. Moreover, this proveds the potentiality of E. camaldulensis for management of heavy metal-contaminated tailings and offers a promising avenue for future environmental restoration.